INVESTIGATION OF “MCM-22”, “ZSM-12 & 35 COMPOSITE”, AND “ZEOLITE AL-MORDENITE & ZSM-39 COMPOSITE” CRYSTALS BY ANALYSIS OF CHARACTERIZATION TECHNIQUES - Kamani, Mina; Rahmati, Masoumehalsadat; Vandani , Samira Amiri Khoshkar; Fard, Ghazaleh Chizari (Journal of the Chilean Chemical Society, 2021)
Zeolites are three-dimensional, microporous, crystalline solids with well-defined structures that contain aluminum, silicon, and oxygen in their form. Cations and water are located in the pores of zeolites. They have a framework structure, in which interconnected cavities are occupied by large metal cations (positively charged ions), and water molecules. The formation of specific zeolites can occur by more than one crystallization pathway. Control in the crystallization pathway can lead to the formation of different species. In this study, two new zeolite nanocomposites were synthesized using fixed raw materials including solvent, reagent (which acts as a template in the formation of zeolite morphology), silica source, and sodium hydroxide alkali. “MCM-22” mesoporous was first synthesized and then a new morphology of “MCM-22” was synthesized by changing the temperature, time, and amount of water. Also, two nanocomposites “ZSM-12 & 35 Composite” and “Zeolite Al-mordenite & ZSM-39 Composite” were synthesized with very different properties in terms of surface to volume ratio, acidity, specific surface area, ratio of Si to Al, and three-dimensional crystal structure. Various characterization techniques were used to provide information to better understand the structural properties of crystalline zeolites. They were then characterized, and analyzed using X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Fourier-Transform Infrared Spectroscopy (FTIR), Energy-Dispersive X-ray Spectroscopy (EDS), Mapping, and BET/BJH (Brunauer-Emmett-Teller (BET) and Barret-Joyner-Halenda (BJH)) techniques. The results showed that the synthetic zeolites, despite having the same precursors, differed in terms of surface to volume ratio, acidity, specific surface area, Si/Al ratio, and three-dimensional crystal structure.